The Evolution of China$1 (Bs Anti-Poverty Strategiess Cases of 20 Chinese Changing Lives - Brown, William N.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This open access book presents the findings of the author$1 (Bs 3 decades of studying China$1 (Bs evolving anti-poverty strategies. It argues that much of the billions that nations spend yearly on economic aid is used inefficiently or to treat the symptoms but not the root causes of poverty. China, however, has evolved an effective sustainable alternative by providing the means for self-reliance to not only relieve economic poverty but also poverty of spirit. As a result, the success of China$1 (Bs historic war on poverty has been due not only to top-down visionary leadership but also to the bottom-up initiatives of an empowered populace unswervingly united in ending poverty. From 1993 to 2019, the author drove over 200,000 km around China and interviewed hundreds of people from all walks of life as he explored the evolution of China$1 (Bs anti-poverty strategies from simplistic aid and redistribution, which often engendered dependency and poverty of spirit. Over time, the philosophy shifted toempowerment by fostering self-reliance$1 (Bor as Chinese put it, (3z(Bblood production rather than blood transfusion.(3y (BThe primary method of empowerment was to provide modern infrastructure, (3z(BRoads first, then riches,(3y (Bso rural dwellers in remote Inner Mongolia or the Himalayan heights of Tibet had the same access to markets, jobs and internet for e-commerce as their urban counterparts. People who seized the opportunities and prospered first then used their newfound wealth and experience to help others. The stories in this book include a Tibetan entrepreneur whose family was impoverished in spite of 300 years of service to the Panchen Lama, or the farm girl with 4 years of education who now has several international schools, a biotechnology company and poverty alleviation projects across China, or the photographer who walked 40,000 km through deserts to chronicle the threat of desertification. Their tales underscore how diverse people across China helped make possible China$1 (Bs success in alleviating absolute poverty and why Chinese are now confident in achieving a (3z(Bmoderately prosperous society.(3y(B.s
Chapter 1: Mogan Mountain$1 (Bs Tang Hairong -- Chapter 2: Liu Yunguang: An Entrepreneur With a Passion for Youth -- Chapter 3: Jing Xuhua $1 (BA Loving Mother Triumphs at Home and in Business -- Chapter 4: Ye Nan Brings a Bright Future to West China -- Chapter 5: Yang Ying$1 (BFrom House Maid to Millionaire Philanthropist -- Chapter 6: Gerile $1 (BMaking Snacks to Put Her Daughter Through College -- Chapter 7: Zhang Fang $1 (BDocumenting Inner Mongolia$1 (Bs Environmental Fight -- Chapter 8: Zhao Xuan, A Retired Teacher From Xi$1 (Ban -- Chapter 9: Bu Wenjun: Inheriting Wei-family$1 (Bs Brick-Carving Craftsmanship -- Chapter 10: Zhang Jianlong $1 (BFrom Migrant Worker to Cattle King -- Chapter 11: Xin Baotong$1 (BHelping the Helpless to Dream Again -- Chapter 12: Wang Zenghao $1 (BYoung Volunteer Working in Tibet -- Chapter 13: Dawa Wangdui: A Tibetan Serf -turned Entrepreneur -- Chapter 14: Xia Jiangping $1 (BGreening the Roof of the World! -- Chapter 15: Wu Qiong ($1-5\"Yc(B) $1 (BEducated to Serve Tibet -- Chapter 16: How Self-made Man Xu Lidao Found He Needed Society -- Chapter 17: Zhu Qingfu $1 (BPassionate About Photography -- Chapter 18: Chen Qiaodi, The Yangshuo of Guangxi -- Chapter 19: Lin Ruiqi, Huawei$1 (Bs Senior Vice President -- Chapter 20: Lucy: The Youthful Heart of Huawei.s
Keywords: China -- History; Quality of life; Economic development; History of China; Quality of Life Research; Development Studies